Pelatihan Product Presentation dalam Training of Trainers Akademisi Pendamping Desa Wisata - Rina Fitriana; Wisnu Bawa Tarunajaya; Andriani Eka Larasati (LPMP Imperium, 2020)
The knowledge about the development of potential products in the tourism village is considered important for every tourism businessmwoman/man because every tourism village in Indonesia has its own potential that if handled properly will be able to become a flagship product. Training of Trainers aims to enhance the understanding and knowledge of academicians who will be mentors in tourist village. This activity was held for 3 days at Santika Premium Dyandra Hotel and Covention Center, Medan City, North Sumatera and followed by 12 offline participants and 3 participants online. The participant consists of academicians from various public and private universities in North Sumatera, West Sumatera, Riau, Riau Islands and Aceh. Training results in the form of increased understanding of participants proved by the result of questionnaire given after the training. 100% (15 participants) stated that this material is very useful for anyone who is involved in tourist villages, although 93% of them (14 participants) feel this material is already common (from further interviews, it is known that most of them have taught courses in marketing). A total of 80% of the participants (i.e. 12 people) stated that the materials provided can be implemented in the tourism village, while 20% (3 participants) believe that the implementation still has many challenges due to the limited soft capacity of the people. Although all participants are satisfied with the material provided, there are 60% (9 participants) who believes that the material will need to be adjusted when used tot rain the people in a tourist village, where there is limited education that may cause this marketing material will not be easily understood by business owners in tourism village. Their input is to give some product examples to show which product presentation that is already good and which product still needs to be repaired. Keywords: Tourist Village, Mentoring, Development of Potential Product, Product Presentation, Training of Trainers